Experimental and Numerical Study the Influence of Sheet Metal Thickness on a Deep Forming Operation of Multi Stages for Hexagonal Cup - AL- Gharrawi, Sabih Salman Dawood; Tuaimah, Ali (Al-Nahrain Journal for Engineering Sciences, 2017)
In this research, experimental and analytical deep drawing of the several-stages design mold is produce hexagonal cup and also proved the influence of the thickness of the sheet on the allocation of strain and laminating in curvature of the cup area for all stages of the drawing. Three stages deep drawing mold was designed and constructed to carry out the experimental work required to produce a hexagonal cup of (28.25 mm by 24.5 mm) , (60 mm) high drawn from a circular flat sheet (80 mm diameter), made from low carbon steel (1006–AISI). Analysis program (ANSYS11.0) to perform the finite element method to accomplish the analytical side of the search. Three types of thickness sheet (